HIGH VARIETY VS LOW VARIETY CULTURE IN THE ARABIC LANGUAGE : THE TENSIONS BETWEEN FUSHí‚ AND ‘í‚MIYYA IN THE CONTEMPORARY ARAB WORLD - Yoyo, Yoyo; Mukhlis, Abdul; Thonthowi, Thonthowi; Ferawati, Ferawati (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
Arabic language, in its sociological context is divided into two varieties: fusha and ‘amiyya. Arabic fusha is the official language and perceived as the language of Islam. In contrast to the fusha, ‘amiyya is the language used by the Arab people in their daily conversations. However, this ‘amiyya is considered as inferior. The method used in this study was qualitative that stressed the interaction between language and its sociological context. The method assumed that social and political events affected language use in a particular society. The paper tries to re-popularize the two terms used by Ferguson that are